Reliability analysis for systems based on degradation rates and hard failure thresholds changing with degradation levels. (December 2021) - Chang, Miaoxin; Huang, Xianzhen; Coolen, Frank P.A.; Coolen-Maturi, Tahani
Highlights: The competing failure processes of the system are divided into multi-state according to degradation levels. The dependency of both degradation rates and hard failure thresholds on the degradation levels is considered. The reliability functions for the system subject to multi-state competing failure processes are derived. The analytical results are compared with the existing literature and the simulation procedures are supplied. The proposed model could be applied to various products and systems experiencing different degradation-shock processes. Abstract: Degradation-shock failure processes widely exist in practice, and extensive work has been carried out to better describe such processes. In this paper, a new model is developed for reliability analysis of systems subject to dependent degradation-shock failure processes. The proposed model extends the previous work by considering the effects of the degradation levels on both the degradation rates and the hard failure thresholds. Instead of shifting with the shock levels, the degradation rates are supposed to increase with the degradation levels, and the hard failure thresholds decrease when the system deteriorates to certain levels. Then, the general reliability functions for the systems subject to multi-state degradation are provided, after deriving the reliability formulas for the systems with two-state degradation. In addition, the accuracy of the proposed methods is verified by Monte-Carlo simulation. Finally, a numerical example is presented to illustrate the validity of the presented model, and analytical results of the proposed model are compared with previous work. The results indicate that the presented method offers a more realistic system reliability evaluation.